ETIKA BISNIS PADA PENJUALAN DENGAN SISTEM OBRAL DI TOKO SEPATU: (Studi Kasus Toko Sepatu Arya Wringinanom, Gresik) - Putri Diana Sari; Hendra Dwi Prasetyo (PUTRA JAWA PUBLISHER, 2023)
This research is motivated by the complexity of sales strategies used by merchants to attract consumer attention, with one of them involving the implementation of a